Enhancement Efficiency of Active Layer P3HT:POT:DBSA/PCBM Photoactive Solar Cell Device - Abdullah A. Hussein (University of Thi-Qar Journal of Science, 2020)
In this work we have investigated thin film blend produced from regioregular poly(3-hexylthiophene) (rr-P3HT), Poly(o-toluidine) doped with dodecylbenzene sulphonic (POT:DBSA) and [6,6]-phenyl-C61 butyric acid methylester (PCBM) materials by spin coating method for application as active layer in photoactive solar cell (PSCs). A thin film uniform rr-P3HT:PCBM and rr-P3HT:POT:DBSA:PCBM were successfully deposited on the poly (3,4 ethylenedioxythiophene): poly (styrenesulfonate) (PEDOT:PSS) buffer layer substrate. The absorption spectra of the films were studied by using UV–vis spectrophotometer and Raman spectroscopy. the morphology of films is evaluated by X-ray diffraction (XRD) and atomic force microscopy (AFM) patterns. We have seen that, the efficiency enhancement for the device with a rr-P3HT:POT:DBSA:PCBM film is more significant than for the device with rr-P3HT:PCBM.